Perlindungan Hukum Terhadap Pelanggaran Hak Cipta Terkait Pembajakan Lagu Mahalini Oleh Rama Chan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The development of information technology today is very rapid, which has a positive and negative impact on law enforcement regarding song copyright which is regulated in Law number 28 of 2014 concerning Copyright. The positive impact is that the flow of any information becomes fast, making it easier to access the latest information also related to the internet which makes it easier to buy original songs/music through online shopping facilities and playing music online on Spotify. Meanwhile, the negative impact is that there are more and more illegal song download links in cyberspace, which also makes it easier to pirate sound recordings in the real world. This research method uses a normative juridical library research method, namely research that refers to legal norms contained in statutory regulations, literature, expert opinions and papers. The result of this study is Copyright protection for creators which has been regulated in the regulations currently in force.